Retroperitoneal semi-closed eversion ring endarterectomy of the left common iliac artery as a bridge for EVAR in a patient with a bilateral obstructive iliac disease - Thomas Kotsis; Aikaterini Kotzadimitriou; Panagitsa Christoforou (Annals of Vascular Surgery - Brief Reports and Innovations, 2023)
Concomitant abdominal aortic aneurysm (AAA) and bilateral iliac occlusive disease constitute a challenge for the application of endovascular repair of the aorta. We present the case of an 84-year-old man with an AAA, coronary disease, intermittent claudication of both legs, comorbidities including a hostile abdomen, and a stent protruding in the aneurysm sac following previous stenting of the right common iliac artery, and with a previous thrombosed axillobifemoral graft. We treated him with a hybrid retroperitoneal technique by placing an aortouniiliac (AUI) stent-graft via an intervening graft-conduit sutured to the bifurcation of the left common iliac artery following a semi-closed eversion ring endarterectomy of the left occluded common iliac artery. The intervening graft was then anastomosed to a new femoral-femoral bypass. The patient is in good condition with all vessels patent for twenty-one months following the operation.